Evaluating Health Literacy Environments in Australian Health Services - Sarah Neil; Kylie Murphy; Glenda Chapman (ACHSM, 2018)
The term 'health literacy' refers to the knowledge and skills used by an individual to make decisions about his or her own health. However, the environment in which health decisions are made is increasingly recognised as a critical component of health literacy. The health literacy environment can help to moderate the typical relationship between low individual health literacy and poor health. Becoming a more health literate healthcare organisation may require only meager financial investment for relatively large effectiveness gains. In this article, a review of Australian government health policies identifies three major foci relevant to the health literacy environment: the complexity of health services, the content of health information, and the physical environment. An overarching theme identified in this review is the importance of consumer input in evaluating all aspects of the health literacy environment. Despite major policy imperatives and the ongoing need to ensure health investments are socially equitable and cost-effective, there is little published evidence of Australian healthcare services evaluating their own health literacy environment. This article establishes the importance of evaluating the health literacy of Australian healthcare services and reviews four potentially useful evaluation tools.